Hemoptysis from an aorto‐pulmonary collateral vessel in a four month old resolved by embolization. Issue 9 (28th April 2016) - Zaidi, Syed Javed H.; Javois, Alexander J.; Akhter, Javeed
Summary: Hemoptysis in the children is a rare but serious diagnosis and is even more uncommon in infancy. Mortality is reported and depends on associated illnesses, underlying etiology, and amount of bleeding. A 4‐month‐old patient presented with significant hemoptysis. Flexible bronchoscopy with differential lavage confirmed the presence and site of origin of hemoptysis. She was managed with cardiac catheterization for embolization of an aorto‐pulmonary collateral vessel with immediate complete resolution and no further recurrences. This highlights the importance of cardiac catheterization to detect collateral vessels as a cause for hemoptysis at this age and its successful resolution following embolization.Pediatr Pulmonol. 2016; 51:E31–E33 . © 2016 Wiley Periodicals, Inc.